Association between Chlamydia Pneumonia Seropositivity and Ischemic Stroke: A Case-Control Study (Bangladesh Journal of Neuroscience, 2017)
Background: Apart from traditional risk factors, infectious agent might contribute to ischemic stroke. The aim of this study was to evaluate the association between Chlamydia pneumonia seropositivity and ischemic stroke.Methods: 42 ischemic stroke patients diagnosed by history, clinical examination and confirmed by CT scan or MRI of brain selected as case. The same number (42) of age and sex matched subjects having no history or clinical evidence of ischemic stroke were selected as control. Blood samples were collected within 2 to 14 days of ischemic stroke from indoor patients. Controls were collected from both indoor and outdoor patients with neurological disorders other than ischemic stroke. Anti-C. pneumoniae antibodies IgG and IgA were detected by ELISA (enzyme-linked immunosorbent assay) in the Department of Virology, Bangabandhu Sheikh Mujib Medical University (BSMMU).Results: Among the study population, 66.7% of cases and 45.2 % of control patients were seropositive to C. Pneumoniae IgG (OR: 2.42, 95% CI: 1.00 - 5.85, p = 0.048). Whereas IgA were positive in 81% of case and 57.1% of control (OR: 3.19, 95% CI: 1.19 - 8.52, p = 0.018). Seropositivity to IgA showed more significant results than IgG.Conclusion: There was a significant association between Chlamydia pneumonia seropositivity both IgG and IgA with ischemic stroke.Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 47-54